Associative Memory Based Image and Object Recognition by Quantum Holography - Loo, Chu Kiong; Peruš, Mitja; Bischof, Horst (2004)
A quantum associative memory, much more natural than those of "quantum computers", is presented. Neural-net-like processing with real-valued variables is transformed into processing with quantum waves. Successful computer simulations of image storage and retrieval are reported. Our Hopfield-like algorithm allows quantum implementation with holographic procedure using present-day quantum-optics techniques. This brings many advantages over classical Hopfield neural nets and quantum computers with logic gates.